(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Migrating crawlers are able to move to the resource which needs to be accessed in order to take advantage of local data access however this process incurs migration cost and have security risks. Therefore to increase the efficiency the crawler must be able to select the best possible server out of multiple copies of a web page present on WWW. In this work a novel credit based server selection mechanism has been proposed for appropriate server selection which considers network parameters like Network distance, Bandwidth availability, and existent load on the server to select a particular server for migrant. This technique provides enhanced security, minimum communication cost and efficient use of network resources.